A personal narration of (Wrena w tarmaiy) Salah Omar, (Daftary piraniy Gamnak) Mardin Eibrahim (Raparin Journal of Humanities (RJH), 2023)
Narration is one of the essential element of a navel. No navel can be written without narration. That’s why it has become an important topic, and the universal literary criticism pays a great deal of attention to it. The study, as (a personal narration of (Wrena w tarmaiy) Salah Omar, (Daftary piraniy Gamnak) Mardin Eibrahim). The entire narration is taken from the Kurdish society and culture. It talks about the pain and suffering of the society.The study is made of two basic parts. Each part is divided in to other sections. The first part, which is the orifical, deals with the definition of narration and its types. The second part, which is practical, studies the relationship of narration with each of the writer, characters and a narrator using examples of different novels. At the end of the study, there is a reference list, abstract and founding.